Pengaruh Brand Ambassador dan Persepsi Kualitas Produk terhadap Minat Pembelian Mahasiswa Pengguna Aplikasi Shopee - Arrum Amalia; Salma Fathiyya Nuha; Khairani Zikrinawati; Zulfa Fahmy (Universitas Katolik Widya Karya Malang, 2023)
Shopee is an e-commerce which is known for frequently changing brand ambassadors with the aim of attracting consumers from all classes and ages. Furthermore, another effort which is made by Shopee is that improve the quality of its products in order to attract more consumers. The aim of this study is that to analyze the influence of brand ambassadors and perceptions of product quality on purchase intention with the subject of student of the Shopee application users. This study used quantitative methods. Moreover, the samples in this study were 107 students who used Shopee application who were selected by using a purposive sampling technique. Meanwhile, the results of the hypothesis were analyzed by using multiple linear regressions. The results of the analysis show that there is no influence of brand ambassadors on purchase intention with a sig value. 0.301 (p>0.05). However, there is an effect of perceived product quality on purchase intention of students who use Shopee application with a Sig. 0.00 (p<0.05). Both of them can simultaneously influence the purchase intention of students who use Shopee application with a large influence seen from the R square coefficient of 36.6% so that the other 63.4% is influenced by other variables.